DEVELOPING A LEAD MAPPING-BASED HARMONIZATION METHODOLOGY FOR FIRST-TIME CONSOLIDATED FINANCIAL REPORTING IN NONPROFIT ORGANIZATIONS - Satria Chandra; Caroline Felicia Christine Lawalata (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Preparing consolidated financial statements for the first time is challenging for nonprofit organizations because parent entities and subsidiaries often apply different financial reporting structures and presentation formats. This study aims to develop a Lead Mapping-Based Harmonization Methodology to support first-time consolidated financial reporting under the Indonesian Financial Accounting Standards for Private Entities (SAK EP). A qualitative case study was conducted using document analysis, interviews, and observation of the consolidation process within a nonprofit group. The findings propose an integrated methodology consisting of four components: (1) a Lead Mapping Framework and Harmonized Group Trial Balance to standardize heterogeneous financial statement presentations; (2) a Matrix Reconciliation to identify and validate reciprocal intra-group transactions before elimination; (3) a Consolidation Reporting Package integrating financial statements and disclosure schedules; and (4) a standardized consolidation workflow. The proposed methodology harmonizes heterogeneous financial reporting structures at the reporting level without requiring changes to entity-specific accounting systems. This study contributes to the literature by providing a practical and replicable harmonization methodology for organizations preparing consolidated financial statements for the first time.